2010
DOI: 10.1074/jbc.m109.057216
|View full text |Cite
|
Sign up to set email alerts
|

The Amyloid Precursor Protein/Protease Nexin 2 Kunitz Inhibitor Domain Is a Highly Specific Substrate of Mesotrypsin

Abstract: The amyloid precursor protein (APP) is a ubiquitously expressed transmembrane adhesion protein and the progenitor of amyloid-␤ peptides. The major splice isoforms of APP expressed by most tissues contain a Kunitz protease inhibitor domain; secreted APP containing this domain is also known as protease nexin 2 and potently inhibits serine proteases, including trypsin and coagulation factors. The atypical human trypsin isoform mesotrypsin is resistant to inhibition by most protein protease inhibitors and cleaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
94
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(105 citation statements)
references
References 67 publications
(95 reference statements)
7
94
0
Order By: Relevance
“…Surprisingly, we found considerable differences between BPTI and APPI in their relative susceptibility to cleavage by mesotrypsin. Whereas APPI was efficiently cleaved by mesotrypsin in seconds, with kinetics resembling those of a good substrate (15), BPTI behaved as a weak temporary inhibitor of mesotrypsin and was only gradually cleaved over the course of hours (22). Mutagenesis studies targeting the canonical binding loops of APPI and BPTI revealed that these differences were not solely determined by the cleavage site sequences, but rather a large proportion of the superior proteolytic stability of BPTI was endemic to the protein scaffold (23), suggesting that the resistance of different Kunitz domains to proteolysis is quite variable.…”
Section: Mesotrypsin Is An Isoform Of Trypsin That Is Uniquely Resistmentioning
confidence: 99%
See 4 more Smart Citations
“…Surprisingly, we found considerable differences between BPTI and APPI in their relative susceptibility to cleavage by mesotrypsin. Whereas APPI was efficiently cleaved by mesotrypsin in seconds, with kinetics resembling those of a good substrate (15), BPTI behaved as a weak temporary inhibitor of mesotrypsin and was only gradually cleaved over the course of hours (22). Mutagenesis studies targeting the canonical binding loops of APPI and BPTI revealed that these differences were not solely determined by the cleavage site sequences, but rather a large proportion of the superior proteolytic stability of BPTI was endemic to the protein scaffold (23), suggesting that the resistance of different Kunitz domains to proteolysis is quite variable.…”
Section: Mesotrypsin Is An Isoform Of Trypsin That Is Uniquely Resistmentioning
confidence: 99%
“…PRSS3 transcripts, primarily encoding trypsinogen 4, are also expressed in many epithelial cells and cancers, and functional studies likewise provide evidence for extracellular roles for active mesotrypsin in tumor progression of breast (8), pancreatic (9), and prostate cancers (10,11). An unusual feature of mesotrypsin is its extreme resistance to endogenous proteinaceous trypsin inhibitors (1,12,13) and its ability to digest some of these inhibitors as substrates (6,14,15). We and others have hypothesized that physiological functions of mesotrypsin may derive from its ability to degrade protein protease inhibitors, for example by digesting plant-derived serine protease inhibitors, such as soy bean trypsin inhibitor in the diet (14), or by degrading the lymphoepithelial Kazal-type inhibitor LEKTI to promote desquamation (6).…”
Section: Mesotrypsin Is An Isoform Of Trypsin That Is Uniquely Resistmentioning
confidence: 99%
See 3 more Smart Citations